Potensi Emisi Gas Rumah Kaca Pengangkutan dan Pengolahan Limbah B3 Infeksius Faskes Surabaya Timur dengan Sistem Dinamik - Nengse, Sulistiya; Warmadewanthi, IDAA (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2024)
Health facilities in East Surabaya consist of 78 facilities, but only 6 have incinerators for processing B3 solid medical waste. Health facilities that do not have incinerators collaborate on transportation and processing with other health facilities that have incinerators or third parties. A dynamic system application is applied to calculate potential Green House Gas (GHG) emissions from the transportation and processing of B3 solid medical waste from health facilities in East Surabaya using a causal loop approach. The research was carried out by measuring medical solid waste generation for 8 days and collecting secondary data. The research includes calculating the weight of medical solid waste and greenhouse gas emissions. The research results show that the weight of medical solid waste increases from year to year with the need for 16 trips per day. The generation of B3 solid medical waste from health facilities in East Surabaya is 5,019 tons/year. With this large generation, the GHG potential from transporting and processing hazardous solid medical waste from health facilities in East Surabaya is 8,200,521 tons CO2e/year.